2021
DOI: 10.1093/pm/pnab070
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the Human Intervertebral Disc: A Scoping Review

Abstract: Objective: Back pain is an elusive symptom complicated by a variety of possible causes, precipitating and maintaining factors, and consequences. Notably, the underlying pathology remains unknown in a significant number of cases. Changes to the intervertebral disc (IVD) have been associated with back pain, leading many to postulate that the IVD may be a direct source of pain, typically referred to as discogenic back pain. Yet, despite decades of research into the neuroanatomy of the IVD, there is a lack of cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 70 publications
0
28
0
5
Order By: Relevance
“…The normal structure of IVD is avascular that is poorly innervated, with the most nerve fibers existing in the outer 1/3 of AF [ 12 ]. In the past few decades, the role and changes of nerve systems during the progression of IVDD have attracted growing attention among researches [ 13 ]. A recent scope review suggested that during the process of IVDD, the neurovascularization within the disc, especially the NP tissue, is gradually evident, which is frequently located at regions of tissue granulation, tears, and lesions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The normal structure of IVD is avascular that is poorly innervated, with the most nerve fibers existing in the outer 1/3 of AF [ 12 ]. In the past few decades, the role and changes of nerve systems during the progression of IVDD have attracted growing attention among researches [ 13 ]. A recent scope review suggested that during the process of IVDD, the neurovascularization within the disc, especially the NP tissue, is gradually evident, which is frequently located at regions of tissue granulation, tears, and lesions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inherently, the native attempt to address IVD injury or tears is through the process of vascularization and innervation into the disc. In healthy discs, nerve fibers, which include perivascular nerves, sensory nerves independent of blood vessels, and mechanoreceptors, appeared only on the surface of the AF 62 . Healthy discs have no substance P‐expressing nerve fibers in the inner AF and NP, which were detected only in degenerated discs 62,63 .…”
Section: Degenerated Np Itself Contributes To Discogenic Painmentioning
confidence: 99%
“…In healthy discs, nerve fibers, which include perivascular nerves, sensory nerves independent of blood vessels, and mechanoreceptors, appeared only on the surface of the AF 62 . Healthy discs have no substance P‐expressing nerve fibers in the inner AF and NP, which were detected only in degenerated discs 62,63 . The invasion of nerves may be the consequence of increased nerve growth factor expression during degeneration 64 .…”
Section: Degenerated Np Itself Contributes To Discogenic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the avascular feature of the ventral NP, the concentration of oxygen, some metabolites, and blood is transported by vascular slumps from the AF to the NP, though the lactic acid concentration and hydrostatic pressure are relatively high [ 13 ]. Nerves commonly travel along the blood vessels, while some of them also develop without blood vessels [ 14 , 15 ].…”
Section: The Structure Overview Of Ivdmentioning
confidence: 99%